PEPTIDE BASED IN SILICO BIORECEPTOR DESIGN FOR DENGUE VIRUS SEROTYPE 2 (DENV-2) NON-STRUCTURAL PROTEIN 1 (NS1) INDONESIA DETECTION - Anugerah Putri, Sherlyna
Dengue fever is a disease caused by the dengue virus (DENV). DENV is divided into four different antigenic serotypes, namely DENV-1, DENV-2, DENV-3, and DENV-4. In Indonesia, dengue fever cases have been increasing since 2021. According to Sasmono et al. (2018), the most prevalent serotype in Indonesia is serotype 2 (DENV-2). This study aims to design a peptide-based bioreceptor for the detection of non-structural protein 1 (NS1) of DENV-2 in Indonesia using in silico methods. The peptide sequence used in this study originated from previous research by Aryati et al. (2013). This study started with the initial design of the peptide obtained from the active site of the crystal structure of the NS1-DENV-2 complex with available antibodies in the Protein Data Bank (PDB). Subsequently, point mutations were performed using the BeAtMuSiC web server to enhance its stability and affinity. The peptide has the sequence EVGYSSYYYYTSPVYLYESG. Molecular docking and molecular dynamics (MD) simulations were used to investigate the affinity and stability of this complex. Molecular docking was conducted to observe the best pose between the peptide and the target protein, utilizing the HADDOCK web server. The binding affinity and dissociation constant (Kd) values were obtained using the PRODIGY web server. The number of interactions was determined using the PDBsum web server. Molecular docking produced three peptides with the best HADDOCK scores, binding affinity, dissociation constant (Kd), and number of interactions. These peptides are Mut 10 (EVGYSSYKYYTSPVYLYEWG), Mut 11 (EVYYS SYEYY TSPVY LYESG), and Mut